COMMON ERRORS FOUND IN THE USE OF SENTENCE STRUCTURE: A CASE STUDY - Desy Chandra; Henny PS Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This study is done to find out: (1) the common errors in the use of sentence structure and (2) the similarities and differences on the types of errors in the use of sentence structure between original draft in the first topic, second topic, and third topic of Written English 4B class English Department in Petra Christian University. The writer chooses the theory of common errors in the use of sentence structure as proposed by Ho (2005). The findings of this study show that there are seven (7) out of eight (8) types of errors that occur in the students’ drafts. Fragmented Sentence is the most common error made by the students in their drafts. In addition, there were similarities and differences on the types of errors and the frequency of occurrences of errors among the students. In conclusion, most of the students have understood about the use of sentence structure.